2021
DOI: 10.5114/wiitm.2021.105530
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of I-125 seed-loaded stent for inoperable hilar cholangiocarcinoma.

Abstract: Introduction Stent insertion is the most frequently used option to treat malignant biliary obstruction (MBO) patients. Hilar cholangiocarcinoma (HCCA) is the most common disease that causes hilar MBO. Aim To assess the clinical efficacy and long-term outcomes of I-125 seed-loaded stent (ISS) insertion for HCCA patients. Material and methods Consecutive patients with HCCA underwent either normal stent (NS) or ISS insertion between January 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The inclusion criteria were patients who: (1) were diagnosed with HC, (2) deemed inoperable, and (3) exhibited obstructive jaundice. The excluded patients were: (1) patients with an Eastern Cooperative Oncology Group performance status of ≥ 3, (2) individuals who have undergone liver resection in the past, (3) patients who have previously received treatment through biliary stent insertion or drainage, and (4) individuals who have declined stent insertion.…”
Section: Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criteria were patients who: (1) were diagnosed with HC, (2) deemed inoperable, and (3) exhibited obstructive jaundice. The excluded patients were: (1) patients with an Eastern Cooperative Oncology Group performance status of ≥ 3, (2) individuals who have undergone liver resection in the past, (3) patients who have previously received treatment through biliary stent insertion or drainage, and (4) individuals who have declined stent insertion.…”
Section: Design and Populationmentioning
confidence: 99%
“…H ilar cholangiocarcinoma (HC) is a prevalent malignant neoplasm, often leading to obstructive jaundice. [1][2][3] However, according to an investigation, 4 it has been shown that a significant proportion, ranging from 70% to 80%, of cases involving individuals with HC are deemed inoperable at the time of diagnosis. The implantation of a stent is considered the primary therapeutic choice for cases with inoperable HC accompanied by obstructive jaundice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, these 125 I seeds can simultaneously deliver a high radiation level to the tumor while mainly avoiding the irradiation of surrounding healthy tissue [4]. A few reports have assessed the relative clinical efficacy of traditional and radioactive stent insertion procedures in patients with HC [9][10][11], but prospective studies on this topic are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Hilar cholangiocarcinoma (HC) is a prevalent malignant tumor involving the hepato-biliary system [1][2][3]. Unfortunately, HC is asymptomatic in the early stages.…”
Section: Introductionmentioning
confidence: 99%